Pengembangan Media Pembelajaran Komik Digital (KODIG) pada Elemen Pemahaman IPAS pada Fase B - Winna Rahmayani; H. Syahrilfuddin; M. Jaya Adi Putra (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This research aims to increase students' reading material about photosynthesis and utilise technology by developing digital comic-based learning media entitled